Intercropping of Jute as Leafy Vegetable With Hybrid Maize Under Different Planting Systems - Begum, AA; Karim, MR; Kakon, SS; Mian, MAK; Rahman, J; Chowdhury, J (Bangladesh Journal of Agricultural Research, 2023)
An experiments were conducted at Agronomy research field, Gazipur and Regional Agricultural Research Station, Jamalpur of Bangladesh Agricultural Research Institute during kharif-1 season of 2018 and 2019 to find out the suitable combination of maize and jute (leafy vegetable) intercropping system for higher productivity and monetary advantage. Treatments included in the experiment were: T1= Hybrid maize normal row (MNR) (60cm × 20cm) + 1 row jute (33%), T2= MNR (60cm × 20cm) + 2 row jute (66%), T3= MNR (60cm × 20cm) + 3 row jute (100%), T4= MNR (60cm × 20cm) + jute broadcast (100%) and T5= Sole maize (60 cm × 20 cm). The experiment was laid out in a randomized complete block design with three replications. At Gazipur, Light availability on jute decreased with the increase of shade produced by maize canopy over the time up to 40 DAS (at harvest of jute) under intercrop situation and the highest light availability was observed on jute in T4 treatment. The maximum grain yield of maize was in sole crop and it was decreased by 1-6 % at Gazipur and 2-9 % at Jamalpur due to intercropping. Maize equivalent yield (MEY) of intercropping treatments showed better performance than sole maize. The highest MEY (19.28 t/ha at Gazipur and 17.41 t/ha at Jamalpur), gross margin (Tk. 252040/ha at Gazipur and Tk. 313380/ha at Jamalpur) and benefit cost ratio (3.65 and 3.33 at Gazipur and Jamalpur, respectively) were observed in T4 treatment among the intercropping treatments. The results revealed that T4 = MNR (60cm × 20cm) + jute broadcast (100%) could be agronomically feasible and economically profitable for maize and jute (leafy vegetable) intercropping system at Gazipur and Jamalpur. Bangladesh J. Agril. Res. 47(3): 269-279, September 2022